Repairing and Strengthening of Damaged RC Columns Using Thin Concrete Jacketing - Bassam A. Tayeh; Mohammed Abu Naja; Samir Shihada; Mohammed Arafa (Advances in Civil Engineering)
This research aims to investigate the efficiency of repairing damaged concrete columns using thin concrete jacketing. The experimental program included casting of nine reference 300 mm long reinforced concrete column specimens: three specimens had a cross-sectional dimension of 100 mm × 100 mm, three specimens had a cross-sectional dimension of 150 mm × 150 mm, and three specimens had a cross-sectional dimension of 170 mm × 170 mm. A total of 36 identical column cores were cast with similar cross sections of 100 mm × 100 mm and a height of 300 mm. These cores were damaged by loading them with approximately 90% of their actual ultimate axial load capacities. Then, the columns were repaired and strengthened by applying two jacketing materials, which were 25 and 35 mm thick, on all four sides. Group 1 consisted of 18 column cores jacketed by normal strength concrete with a maximum aggregate size of 4.75 mm and steel reinforcement, whereas Group 2 consisted of 18 column cores jacketed using ultrahigh-performance fibre-reinforced self-compacting concrete with steel reinforcement. The experimental program showed that the Group 1 specimens had ultimate load capacities more than twice those of the unjacketed reference columns and the same axial capacity as the monolithically cast reference columns. The Group 2 specimens showed a significant increase in ultimate load capacity, which was approximately 3 times that of the unjacketed reference column and 1.86 times that of the monolithically cast reference columns. Moreover, using the shear studs was found to be the most effective among the three surface preparation techniques.